Impact of Early Diagnostic and Therapeutic Interventions and Clinical Course in Children and Adolescents with Multiple Endocrine Neoplasia Types 1 and 2 - Kim, Ja Hye; Lee, Yena; Hwang, Soojin; Yoon, Ji-Hee; Kim, Gu-Hwan; Yoo, Han-Wook; Choi, Jin-Ho (Experimental and Clinical Endocrinology & Diabetes, 2023)
Purpose Multiple endocrine neoplasia types 1 (MEN1) and 2 (MEN2) are inherited endocrine tumor syndromes caused by mutations in the MEN1 or RET genes. This study aimed to investigate clinical outcomes and molecular characteristics among children with MEN.Methods This study included eight patients from seven unrelated families. Data on clinical course, biochemical findings, and radiologic studies were collected by retrospective chart review. All diagnoses were genetically confirmed by Sanger sequencing of MEN1 in three MEN1 patients and RET in four patients with MEN2A and one patient with MEN2B.Results Three patients with MEN1 from two families presented with hypoglycemia at a mean age of 11±2.6 years. Four patients with MEN2A were genetically diagnosed at a mean of 3.0±2.2 years of age by family screening; one of them was prenatally diagnosed by chorionic villus sampling. Three patients with MEN2A underwent prophylactic thyroidectomy from 5 to 6 years of age, whereas one patient refused surgery. The patient with MEN2B presented with a tongue neuroma and medullary thyroid carcinoma at 6 years of age. Subsequently, he underwent a subtotal colectomy because of bowel perforation and submucosal ganglioneuromatosis at 18 years of age.Conclusion This study described the relatively long clinical course of pediatric MEN with a mean follow-up duration of 7.5±3.8 years. Insulinoma was the first manifestation in children with MEN1. Early diagnosis by family screening during the asymptomatic period enabled early intervention. The patient with MEN2B exhibited the most aggressive clinical course.
Keywords: insulinoma; MEN1; multiple endocrine neoplasia; RET; proto-oncogene; medullary thyroid cancer